Nonlinear electric conduction of CCTO/EPDM composites used for reinforced insulation in cable accessory - Li, Zhongyuan; Zhang, Jian; Chen, Shiyu; Liu, Heqian; Wang, Lei; Liang, Jianquan; Zhang, Kexin; Zhang, Peng; Sun, Weifeng (Frontiers in Energy Research, 2023)
Nonlinear electric conductance of reinforced insulation can homogenize electric field distribution and suppress local electric field distortion inside high-voltage direct current cable accessories. To achieve a significant nonlinear electric conductance in ethylene–propylene–diene misch–polymere (EPDM) used for reinforced insulation of cable accessories, the inorganic micron crystal powder of calcium copper titanate (CCTO) is synthesized by the sol–gel method, which is filled into EPDM to prepare 5∼15 wt% CCTO/EPDM composites by melting blend and hot-press molding methods. Microscopic structure, electric conductivity, direct current (DC) dielectric breakdown strength, and charge trap characteristics of CCTO/EPDM composites are tested to reveal the underlying derivation of electric conduction nonlinearity. Scanning electron microscopy and X-ray diffraction (XRD) demonstrate that CCTO micron fillers are uniformly dispersed in the EPDM matrix. Dielectric breakdown strength of CCTO/EPDM composites gradually decreases with the increase in CCTO content while persisting qualified for electrical insulation of DC cable accessories. CCTO crystal macron fillers introduce shallower charge traps than the intrinsic charge traps derived from the structural defect EPDM matrix, which initiates the percolating conductive channels between charge traps under high electric fields, accounting for the significant nonlinearity in the profile of electric current density versus electric field strength. Finite-element simulations and analyses on the electrostatic field in DC cable terminals prove that employing 15 wt% CCTO/EPDM composite as reinforced insulation can efficiently homogenize the electric field at the interface between the main insulation and accessory insulation of power cables, which is of great interest to develop insulation materials used for DC cable accessories in severe environments.